2018
DOI: 10.1080/1354750x.2018.1427794
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual variation of miRNA expression levels in human plasma samples

Abstract: Background Circulating miRNAs as potential non-invasive biomarkers for disease risk assessment and cancer early diagnosis have attracted increasing interest. Little information, however, is available regarding the intra-individual variation of circulating miRNA levels. Methods We measured expression levels of a panel of 800 miRNAs in repeated plasma samples from 51 healthy individuals that were collected 6 to 12 months apart and evaluated the intra-individual variation by the intra-class correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, we studied knee OA in women only, and the number of participants is limited. It has been demonstrated that gender may influence the level of the expression of miRNAs [52]. Consequently, our results need to be confirmed by additional larger studies and particularly in males.…”
Section: Discussionmentioning
confidence: 65%
“…However, we studied knee OA in women only, and the number of participants is limited. It has been demonstrated that gender may influence the level of the expression of miRNAs [52]. Consequently, our results need to be confirmed by additional larger studies and particularly in males.…”
Section: Discussionmentioning
confidence: 65%
“…Recent advances within the field of sequencing (SLAM-seq [ 69 ]) using tissue-specific incorporation of 4-thiouridine (4-TU) could prove useful for in vivo tracking of miRNAs released into circulation. Despite miRNA levels demonstrating high correlations between repeated samples over a larger sampling period in healthy individuals [ 70 , 71 ], more longitudinal studies within pregnant women are needed should miRNAs be utilized in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of 75 miRs revealed an intra-class coefficient (ICC) of > 0.5 when analysed in a subject at two time points 6 to 12 months apart, suggesting reasonable similarity, with a median ICC of 0.4 for the total 185 miRs. Notably, ICC was higher for miRs with higher plasma levels or higher detection rates (Wu et al 2018b).…”
Section: Inter-and Intra-individual Variability In Basal Mir Expressionmentioning
confidence: 96%
“…For miR measurements to be reliable indicators of injury, a good understanding of the presence and significance of variation in their basal levels is required. Intra-individual variation has been assessed by Wu et al (2018b), where circulating miR levels in repeated samples were collected from fifty-one healthy volunteers over a 6-12-month period. 185 miRs were detected in at least 10% of plasma samples, 69 in 50% and 28 in 90%.…”
Section: Inter-and Intra-individual Variability In Basal Mir Expressionmentioning
confidence: 99%